Couplex Benchmark Computations Obtained with the Software Toolbox UG - Bastian, Peter; Lang, Stefan (Computational geosciences, 2004)
Issue Title: Simulation of Transport Around a Nuclear Waste Disposal Site: The COUPLEX Test Cases This paper describes the numerical results for the COUPLEX benchmark obtained with the simulation software UG using vertex centered finite volume and higher order discontinuous Galerkin schemes. Multigrid solvers on unstructured grids, local mesh refinement and parallel computation are employed to yield very accurate solutions. Since the full range of results required in the benchmarks is too large to be displayed in this paper we focus on the comparison of discretization schemes, assessment of numerical errors and the presentation of parallel computations.[PUBLICATION ABSTRACT]